2015
DOI: 10.1007/s13277-015-3305-6
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26b inhibits metastasis of osteosarcoma via targeting CTGF and Smad1

Abstract: Downregulation of miR-26b has been found in various cancers, but it has never been investigated in osteosarcoma. In this study, we demonstrated downregulation of miR-26b in osteosarcoma tissues, negatively correlated with the expression of connective tissue growth factor (CTGF) and Smad1. Luciferase reporter assay confirmed the interaction of miR-26b with the 3' untranslated regions (UTRs) of CTGF and Smad1. Transfection of miR-26b in osteosarcoma cells suppressed the expression of CTGF and Smad1, suggesting C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Additionally, miR-26b-5p mimic inhibited Col1a2 and CTGF expression at the post-transcriptional level in cardiac fibroblasts. The present conclusion has been partially supported by previous studies showing that CTGF is a target of miR-26b in osteosarcoma cells35 and in pulmonary artery smooth muscle cells36, respectively. Importantly, our present data validated that circRNA_000203 specifically eliminates the interactions of miR-26b-5p with the 3′-UTRs of Col1a2 and CTGF, and impairs the inhibitory effect of miR-26b-5p on the fibrosis-associated genes, including Col1a2, Col3a1, α-SMA and CTGF, in cardiac fibroblasts.…”
Section: Disccusionsupporting
confidence: 87%
“…Additionally, miR-26b-5p mimic inhibited Col1a2 and CTGF expression at the post-transcriptional level in cardiac fibroblasts. The present conclusion has been partially supported by previous studies showing that CTGF is a target of miR-26b in osteosarcoma cells35 and in pulmonary artery smooth muscle cells36, respectively. Importantly, our present data validated that circRNA_000203 specifically eliminates the interactions of miR-26b-5p with the 3′-UTRs of Col1a2 and CTGF, and impairs the inhibitory effect of miR-26b-5p on the fibrosis-associated genes, including Col1a2, Col3a1, α-SMA and CTGF, in cardiac fibroblasts.…”
Section: Disccusionsupporting
confidence: 87%
“…One study reported inclusion and exclusion criteria [39]. Six studies reported randomization [39, 46, 47, 55, 58, 65], whereas 23 studies reported potential conflicts of interest and study funding [25, 33, 36, 37, 39, 40, 43, 44, 46-48, 50, 52-58, 60-62, 64]. Only one study reported blinded assessment of outcome [53].…”
Section: Resultsmentioning
confidence: 99%
“…There were 40 mice in the intervention arm and 57 in the control arm. The tumor volume significantly reduced when the decreased tumor suppressor miRNAs were corrected (pooled MD = [ -4.01]; 95% confidence interval [CI]: [-5.89]- [-2.13]; p < 0.00001; Figure 8A, part 2)in a random-effects model [33, 35, 36, 60, 63, 64]. MiRNAs were infected into the OS cells by lentivirus vectors in 8 studies, and were combined for a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…La-related protein 1 (LARP1) was identified as a regulatory target of miR-26a/b inhibiting prostate cancer (PCa) cell invasion by Kato et al [37]. Duan and co-workers found that downregulation of miR-26b in osteosarcoma elevates the levels of CTGF and Smad1, facilitating metastasis in osteosarcoma (os) [27]. Reduced miR-26b expression promoted breast fibroblast migration and invasion.…”
Section: Discussionmentioning
confidence: 99%